First record of the orchid bee Euglossa imperialis Cockerell, 1922 (Hymenoptera, Apidae, Euglossina) in Mato Grosso do Sul state, midwestern Brazil - Jessica Amaral Henrique; Ana Isabel Sobreiro; Valter Vieira Alves-Júnior (Check List, 2018)
The occurrence of Euglossa imperialis Cockerell, 1922 is recorded for the first time in Mato Grosso do Sul, Brazil. This paper extends the distribution of the species by about 800 km west of the São Paulo state, its nearest record.